THE EFFECT OF MINDFULNESS ON ACADEMIC SELF-EFFICACY: A RANDOMISED CONTROLLED TRIAL - Jack R. Menges; Marie L. Caltabiano (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study examined the effect of a brief mindfulness intervention on academic self-efficacy. Twenty-six university students were randomised to a four day brief mindfulness intervention or a wait-listed control condition. The brief mindfulness intervention took the form of four 30 minute sessions of mindfulness meditation over four consecutive days. Measures of mindfulness, emotional wellbeing and academic self-efficacy were obtained via a self-report survey prior to the intervention, post-intervention and at one month follow-up. Both groups had comparable baseline measures on all three scales. Data analysis revealed that both academic self-efficacy and mindfulness increased between pre- and post-intervention with a medium effect size (d = 0.472 and 0.415 respectively). Emotional wellbeing significantly increased following the intervention with a large effect size (d = 0.652) and remained at this level after one month. Academic self-efficacy also stayed at elevated post-intervention levels after one month while mindfulness continued to increase following the intervention and was significantly higher at follow-up than at baseline (d = 0.564). There were no significant changes in the measured variables for the control group. Regression analysis revealed that increases in emotional wellbeing significantly predicted increases in academic self-efficacy for participants in the experimental group, both increases in mindfulness and emotional wellbeing were significantly correlated with increases in academic self-efficacy. These findings suggest that a brief mindfulness intervention is an effective and practical means to improve academic self-efficacy and emotional wellbeing in university students. Implications, limitations and future directions for research are discussed.